Evaluation of new stream ciphers for multimedia systems - Castro, Vanessa Rose.; Marifosque, Jan Arvin; Wyson, James (2008.)
Current mobile devices provide us means of capturing, sending and receiving multimedia files without connecting them to a personal computer. The price of having such powerful tools is the easy transfer of copyrighted or private multimedia files. As a solution, the use of cryptography, which provides confidentiality, ensures integrity and gives authenticity to the sender and receiver of the files is suggested. Cryptography can be applied using cryptosystems such as block and stream ciphers. Five promising stream ciphers from the eStream project were tested, evaluated and benchmarked for their speed, efficiency and memory usage. Additionally, they were used in still image multimedia encryption algorithms, selective encryption of DCT coefficients for JPEG and bitplane encryption for PNG. Results show that modern stream ciphers provide relatively the same security as block ciphers running in stream mode while running significantly faster.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Ciphers; Data transmission systems -- Security measures; Cryptography; Stream ciphers